Global challenges with scale-up of the integrated management of childhood illness strategy: results of a multi-country survey - Muhe Lulu M; Goga Ameena E (BMC, 2011)
Abstract Background The Integrated Management of Childhood Illness Strategy (IMCI), developed by WHO/UNICEF, aims to contribute to reducing childhood morbidity and mortality (MDG4) in resource-limited settings. Since 1996 more than 100 countries have adopted IMCI. IMCI case management training (ICMT) is one of three IMCI components and training is usually residential over 11 consecutive days. Follow-up after ICMT is an essential part of training. We describe the barriers to rapid acceleration of ICMT and review country perspectives on how to address these barriers. Methods A multi-country exploratory cross-sectional questionnaire survey of in-service ICMT approaches, using quantitative and qualitative methods, was conducted in 2006-7: 27 countries were purposively selected from all six WHO regions. Data for this paper are from three questionnaires (QA, QB and QC), distributed to selected national focal IMCI persons/programme officers, course directors/facilitators and IMCI trainees respectively. QC only gathered data on experiences with IMCI follow-up. Results 33 QA, 163 QB and 272 QC were received. The commonest challenges to ICMT scale-up relate to funding (high cost and long duration of the residential ICMT), poor literacy of health workers, differing opinions about the role of IMCI in improving child health, lack of political support, frequent changes in staff or rules at Ministries of Health and lack of skilled facilitators. Countries addressed these challenges in several ways including increased advocacy, developing strategic linkages with other priorities, intensifying pre-service training, re-distribution of funds and shortening course duration. The commonest challenges to follow-up after ICMT were lack of funding (93.1% of respondents), inadequate funds for travelling or planning (75.9% and 44.8% respectively), lack of gas for travelling (41.4%), inadequately trained or few supervisors (41.4%) and inadequate job aids for follow-up (27.6%). Countries addressed these by piggy backing IMCI follow-up with routine supervisory visits. Conclusions Financial challenges to ICMT scale-up and follow-up after training are common. As IMCI is accepted globally as one of the key strategies to meet MDG4 several steps need to be taken to facilitate rapid acceleration of ICMT, including reviewing core competencies followed by competency-driven shortened training duration or 'on the job' training, 'distance learning' or training using mobile phones. Linkages with other 'better-funded' programmes e.g. HIV or malaria need to be improved. Routine Primary Health Care (PHC) supervision needs to include follow-up after ICMT.